#Arttothepeople? An exploration of Instagram's unfulfilled potential for democratising museums. (2nd November 2022) - Bosello, Greta; van den Haak, Marcel
ABSTRACT: Today, most museums in Europe and the United States present themselves as democratic institutions. Meanwhile, scholarly literature puts much emphasis on the democratising potential of social media for museum practice. Prompted by the scarcity of factual data on museums' employment of social media, this article presents an empirical study on how art museums use Instagram. Specifically, the research focuses on the extent to, and the ways in which, art museums are harnessing Instagram in order to fulfil their democratic aspirations. Through content analysis, the study shows that Instagram's potential for a more democratic museology is being harnessed to a very limited extent. Museums predominantly use Instagram for more traditional promotional purposes or adopt an authoritative knowledge-telling attitude in their posts. Nevertheless, we present several promising exceptions, that we analyse through close reading. These examples pave the way to a more democratic museum practice on Instagram.